Electrocardiographic parameters effectively predict ventricular tachycardia/fibrillation in acute phase and abnormal cardiac function in chronic phase of ST‐segment elevation myocardial infarction. (28th February 2018) - Yu, Ziqing; Chen, Zhangwei; Wu, Yuan; Chen, Ruizhen; Li, Minghui; Chen, Xueying; Qin, Shengmei; Liang, Yixiu; Su, Yangang; Ge, Junbo
Abstract: Background: Abnormal cardiac repolarization is closely associated with ventricular tachycardia/ventricular fibrillation (VT/VF). Myocardial ischemia and infarction aggravate cardiac repolarization dispersion, and VT/VF could be lethal in the early stage of ST‐segment elevation myocardial infarction (STEMI). Unfortunately, VT/VF cannot be effectively predicted in current clinical practice. The present study aimed to assess electrocardiographic parameters of the sinus rhythmic complex in relation to cardiac repolarization, e.g., QT interval and T‐peak to T‐end interval (TpTe), to independently predict VT/VF in acute STEMI. Additionally, we hypothesized that QT and TpTe of PVC would be also valuable to predict VT/VF in STEMI. Methods and results: A total of 198 cases diagnosed as STEMI with PVC on admission by electrography were included. During hospitalization, VT/VF values were recorded. Logistic analysis was performed between patients with and without VT/VF to validate independent electrocardiographic predictors. QTcPVC interval > 520 ms (OR = 3.2; P = 0.027), TpTe interval > 100 ms (OR = 3.1; P = 0.04), TpTePVC  > 101 ms (OR = 3.6; P = 0.029), TpTe/QT > 0.258 (OR = 5.7; P = 0.003), and TpTe/QTPVC  > 0.253 (OR = 3; P = 0.048). However, QRS duration, QTc interval, coupling interval, and QRSPVC duration did not predict VT/VF. Besides, QRSPVC duration >140 ms (OR = 2.6; P = 0.001) independently predicted LVEF decrease after 1 year or more. Conclusions: QTcPVC interval, TpTe interval, TpTePVC interval, TpTe/QT ratio, and TpTe/QTPVC ratio are risk factors for ECG independent from other confounding factors in predicting VT/VF in the acute phase of STEMI. In addition, PVC characteristics as risk factors for VT/VF in acute phase and LVEF decrease in chronic phase were firstly reported.